Is There an Association Between Prophylactic Femur Stabilization and Survival in Patients with Metastatic Bone Disease? - Philipp, Travis C. (Clin Orthop Relat Res, 2020)
BACKGROUND: The femur is the most common site of metastasis in the appendicular skeleton, and metastatic bone disease negatively influences quality of life. Orthopaedic surgeons are often faced with deciding whether to prophylactically stabilize an impending fracture, and it is unclear if prophylactic fixation increases the likelihood of survival. QUESTIONS/PURPOSES: Is prophylactic femur stabilization in patients with metastatic disease associated with different overall survival than fixation of a complete pathologic fracture? METHODS: We performed a retrospective, comparative study using the national Veterans Administration database. All patient records from September 30, 2010 to October 1, 2015 were queried. Only nonarthroplasty procedures were included. The final study sample included 950 patients (94% males); 362 (38%) received prophylactic stabilization of a femoral lesion, and 588 patients (62%) underwent fixation of a pathologic femur fracture. Mean followup duration was 2 years (range, 0-7 years). We created prophylactic stabilization and pathologic fracture fixation groups for comparison using Common Procedural Terminology and ICD-9 codes. The primary endpoint of the analysis was overall survival. Univariate survival was estimated using the Kaplan-Meier method; between-group differences were compared using the log-rank test. Covariate data were used to create a multivariate Cox proportional hazards model for survival to adjust for confounders in the two groups, including Gagne comorbidity score and cancer type. RESULTS: After adjusting for comorbidities and cancer type, we found that patients treated with prophylactic stabilization had a lower risk of death than did patients treated for pathologic femur fracture (hazard ratio = 0.75, 95% CI, 0.62–0.89; p = 0.002). CONCLUSIONS: In the national Veterans Administration database, we found greater overall survival between patients undergoing prophylactic stabilization of metastatic femoral lesions and those with fixation of complete pathologic fractures. We could not determine the cause of this association, and it is possible, if not likely, that patients treated for fracture had more aggressive disease causing the fracture than did those undergoing prophylactic stabilization. Currently, most orthopaedic surgeons who treat pathological fractures stabilize the fracture prophylactically when reasonable to do so. We may be improving survival in addition to preventing a pathological fracture; further study is needed to determine whether the association is cause-and-effect and whether additional efforts to identify and treat at-risk lesions improves patient outcomes. LEVEL OF EVIDENCE: Level III, therapeutic study.